Analysis of Student's Answer Error on Understanding of Energy Concept in Conceptual Change Text (CCT)-Based Learning - Rahmah Novianti; Wafa Nur Aisyah; Wati Sukmawati (Postgraduate, University of Mataram, 2023)
Science learning has been considered a difficult subject for students. This study aims to analyze student error answers on students' science understanding abilities on energy concepts to find out students' difficulties in answering energy concept science questions through Conceptual Change Text (CCT) based learning. This CCT-based learning requires students to be more active in understanding concepts with the help of reading materials that have been provided by the teacher so that students can find concepts independently. The reading material given to students is in the form of reading material about energy. This research was conducted on third, fourth, and fifth-grade elementary school students to determine the level of difficulty at each level. This research method is a qualitative method using grounded theory. The instrument used is a test instrument. Student answer sheets to analyze the types of errors made by students in accordance with the energy concept learning indicators. Based on the results of the survey, data were collected on the average error rate of students in grades 3, 4, and 5 on energy concepts. The data shows that the third grade has an average error of 30.34%, the fourth-grade student's average error is 21.64%, and the fifth-grade student's average error is 14.39%.